A Long Hello to Beveridge : social security in the Republic of Ireland, 1981 - 2007 - McCashin, Anthony (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2015)
This thesis analysed the development of social security in the Republic of Ireland from 1981 to 2007, by providing a theoretically informed account of changes in expenditure, law and policy. The central argument of the thesis is that social security in Ireland was not simply emasculated in the face of globalisation and related pressures. To the contrary, there is evidence of expansion and improvement, as well as evidence of retrenchment. On the whole, social security was a more encompassing system in 2007 than in 1981, and for some, more generous. Internationally, scholars have identified retrenchment and other forms of restructuring of social security in advanced welfare states, notably those in the Anglo-Saxon 'world of welfare' This thesis offers a comprehensive analysis of social security in Ireland from 1981 to 2007 and shows that social security there adapted, but in complex ways that resulted in considerable continuity. Globalisation did not exert a direct, downward pressure on social security in Ireland, and the sources of change were both national and global. As in other small welfare states, national institutions and politics mediate and structure change, and are particularly important in understanding social security developments. In Ireland's case, over the time span of this study, change took a variety of forms; cost containment and retrenchment, but also modernisation and expansion, all within the context of a continuing commitment to a system of national insurance.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin